Diversity of the genus Tropodiaptomus Kiefer, 1932 (Crustacea, Copepoda, Calanoida, Diaptomidae) in Thailand, with the description of two new species - Thanida Saetang; Supiyanit Maiphae (Zoosystematics and Evolution, 2023)
Tropodiaptomus is a genus of diaptomid copepods with 10 species currently recorded in Thailand. A recent study on DNA taxonomy revealed putative new species among specimens collected from freshwater habitats throughout Thailand. This study examined the morphological characteristics and confirmed the taxonomic status of the two putative new species of Tropodiaptomus. Results showed that the two new taxa were different from other species in the genus Tropodiaptomus. These two new species, T. pedecrassum sp. nov. and T. longiprocessus sp. nov., were described and illustrated based on material collected from a swamp in northern Thailand and a pond in western Thailand, respectively. They were distinguished from their congeners by the length of the spinous process on the antepenultimate segment of the adult male right antennule, the number of lobes and serration pattern on the inner margin of the adult male left P5, and the shape and supplementary process on the surface structures of basis and distal exopod segments of the adult male right P5. These discoveries increased the number of records of this genus in Thailand to 12 species. A pictorial key to all species is provided, and their ecological and biogeographical distributions are updated and discussed.